Introduction to counselling skills texts and activities - Nelson-Jones, Richard 1936- (SAGE Publications, 2013)
Good counseling skills are the key to effective helping relationships. Introduction to counselling skills, second edition, is designed to help readers acquire and develop these skills, using an easy, three-stage model. Drawing on many years experience as a counselor, trainer and writer, Richard Nelson-Jones describes in detail each stage in the helping process and gives examples to show how the skills work in practice. The examples also demonstrate the variety of contexts in which counseling skills are commonly used, as well as the diversity of issues and problems they can help to address. The book covers: what counselling skills are; how to conduct sessions; ways to clarify and expand your understanding; how to improve your listening skills; and ethical skills. Introduction to counselling skills, second edition, is full of practical features designed to aid learning, including activities related to the particular skill being described, learning outcomes, examples, summaries, and a glossary of key terms. For this, the second edition, the book has been fully up-dated and new material has been added on the diversity of helpers and clients, the use of training groups and supervision. Combining a clear explanation of skills with a host of practical activities, Introduction to counselling skills, second edition, is the ideal text for introductory courses in counselling skills, counselling and many other professional areas including health care, management, education and social work.